EFFECTS OF FOREIGN LOANS, INTEREST RATE, AND EXPORT FOR THE FOREIGN EXCHANGE RESERVES IN INDONESIA 2002-2016 - Anas Iswanto Anwar; Bayu Pamungkas Djamal; Sri Undai Nurbayani (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2019)
The aim of this research is to analyze the effect of foreign loans, interest rate, and export for the foreign exchange reserves in Indonesia during 2002-2016. This research used secondary data which tends the time-series published by Bank Indonesia, The Ministry of Trade Republic of Indonesia, Central Agency on Statistics Indonesia in the year of 2002-2016. The result of the regression by using ordinary least squares (OLS) method showed that the foreign loans and export take effect positively to the foreign exchange reserves. It indicates that the increase of foreign loans and export could affect the foreign exchange reserves in Indonesia during 2002-2016. Otherwise, the interest rate could not affect the foreign exchange reserves in Indonesia during 2002-2016.